Reflexões sobre a aplicação da gestão do conhecimento pelas universidades: o caso da Escola de Engenharia da Universidade Federal Fluminense - Antunes, Liane Regina Maggioni Silva (2008)
The Universities are central institutions in the process of creation and transmission of the knowledge and, each time more, are urged to contribute to the increase of innovation and the technological development of the region they are situated. In order to be able for the attendance of this requirement, they must reevaluate their politics and management models, trying to be more flexible and more up to date, actions that will guarantee more efficiency and effectiveness in their processes. The principles of the knowledge management applied by the universities can provide the improvement of the education, research and extension. In consequence, the management of these institutions must approach the knowledge as raw material, factor of production and product, adding value to each development stage. This study has as objective the analyze of Knowledge Management based on the principles of Constructive Elements proposed by Probst, Raub and Romhardt (2002), and considering the Seven Dimensions of Knowledge Management described by Terra (2001), at Universidade Federal Fluminense , especially at Escola de Engenharia . This study intends to check if the possible actions of Knowledge Management are linked to the institutional strategy to develop organizational competences, as well as protect competitive advantages. It is presented a study on the administration and identification of positive points and the ones which need improvement. In addition, it is supposed to give the managers information to add value to future initiatives related to Knowledge Management. The work is concluded proving that the identified actions, although not intentionally formalized and defined as a mechanism of knowledge management officially instituted by the direction of the Escola de Engenharia , are, in fact, linked to the institutional strategy and can lead to the improvement of its processes and the development of organizational abilities, fortifying the Institution in order to get sustainable competitive differential.